T-Scan Novus System in the Management of Splints—Pilot Study - Bozhkova, Tanya; Shopova, Dobromira (European Journal of Dentistry, 2021)
The purpose of this pilot study was to demonstrate the capabilities of the T-Scan Novus system in bruxism treatment by splints. Bruxism patients underwent treatment with a splint made by additive manufacturing. Intraoral scanning was performed using Trios Color (3Shape), and digital design was performed using 3Shape Dental system design - splint studio. The biocompatible material Dental LT Clear Resin was printed using a Formlabs Form 2 printer. The T-Scan Novus system with a software attached to it, version 9.1, was used for digital examination of the occlusion. A splint with an occlusal thickness of 2.5 mm was developed and software adapted with relief to antagonists. The digitally set occlusion with even contacts turned out to be clinically unbalanced. After adjusting with T-Scan Novus, a balanced occlusion was achieved in the right and left halves. The treatment of bruxism with splint therapy continues to be the main method. Its combination with digital technologies allows more precise constructions and more accurate balancing of occlusal relationships.
Keywords: 3Shape; splint; bruxism; digital splint design; T-Scan Novus system